Bullying in Classrooms: The Role of Parental Physical and Psychological Aggression (Medical Forum Monthly, 2024)
Objective: To investigate the relation of parental education and their physical and psychological aggression towards children, and to explore the impact of parental aggression (Physical and psychological) on classroom bullying.Study Design: Observational / descriptive study.Place and Duration of Study: This study was conducted at the Secondary schools of Mansehra, Abbotabad, and Haripur Districts of Hazara Division from October, 2013 to March, 2014.Materials and Methods: A sample of 1438 was selected to collect data by using two questionnaires. One questionnaire was about Bullying while the other was about parental aggression. Analysis of collected was done through mean, standard Deviation, and multiple regression model using SPSS 20 version.Results: The mean and standard deviation value of physical aggression of parents was (3.96+1.23) while that of psychological aggression was (3.97+1.08). Additionally, the education level of father was negatively correlated with their physical aggression (r=-0.29, α=0.000) as well as psychological aggression (r=-0.28, α=0.000). Similarly, mothers’ level of education was significantly negatively correlated with both physical aggression (r=-0.16, α=0.000) and psychological aggression (r=-0.14, α=0.000). The results further indicated that parental physical aggression (β=0.16, t=5.20, α=0.000) positively predicted classroom bullying.Conclusion: The highly educated parents show less aggression towards their children. Aggressive behavior of parents paves the way for their children to become victims of bullying in classroom.